Positive association between cardiometabolic index and gallstones, with greater impact on women and those younger than 50 years: the NHANES 2017–2020 cross-sectional study - Jing Zheng; Huqiang Dong; Hongli Wan; Qingye Yang; Shujuan Xu; Tingting Hu; Chang Fu; Keyun Cheng (BMC Public Health)
Abstract Background Gallstones are a common hepatobiliary disorder. It is unclear whether cardiometabolic index (CMI) is associated with gallstones. The purpose of this study was to examine the association between CMI levels and gallstone prevalence among US adults. Methods We investigated data from 3711 participants aged 20 years or older in the 2017–2020 National Health and Nutrition Examination Survey (NHANES). Confounder adjustment, multivariate logistic regression modeling, and restricted cubic spline (RCS) analyses were used to assess the association between CMI and gallstone prevalence, and threshold effect analyses were performed. We conducted subgroup analyses to evaluate the impact of confounding variables, including age and gender. A sensitivity analysis was also performed to increase the robustness of the results. Results The weighted prevalence of gallstones in this study was 11.04%. The risk of gallstones increased significantly with higher CMI quartiles. Logistic regression analysis showed that there was a significant positive correlation between CMI and the risk of gallstones, with a 5% increase in the risk of gallstones for each one-unit increase in CMI (OR = 1.05). In the adjusted model, the positive correlation between CMI and the risk of gallstones remained significant. RCS analysis showed a nonlinear relationship between CMI and gallstones, with an inflection point of 0.69. Subgroup analyses showed that elevated CMI was significantly associated with the risk of gallstones in females and in the 20–50 year old population. Conclusion As the first study to show a significant association between CMI and the occurrence of gallstones in an adult population in the United States. However, further longitudinal studies are needed to verify this association.